Effects of annealing on the properties of gamma-irradiated sago starch - Lee, Jau-Shya; Jahurul Haque Akanda; Fong, Soon Loong; Siew, Chee Kiong; Ho, Ai Ling (Molecular Diversity Preservation International, 2022)
The increase in health and safety concerns regarding chemical modification in recent years has caused a growing research interest in the modification of starch by physical techniques. There has been a growing trend toward using a combination of treatments in starch modification in producing desirable functional properties to widen the application of a specific starch. In this study, a novel combination of gamma irradiation and annealing (ANN) was used to modify sago starch (Metroxylon sagu). The starch was subjected to gamma irradiation (5, 10, 25, 50 kGy) prior to ANN at 5 °C (To-5) and 10 °C (To-10) below the gelatinization temperature. Determination of amylose content, pH, carboxyl content, FTIR (Fourier Transform Infrared) intensity ratio (R1047/1022), swelling power and solubility, thermal behavior, pasting properties, and morphology were carried out. Annealing irradiated starch at To-5 promoted more crystalline perfection as compared to To-10, particularly when combined with 25 and 50 kGy, whereby a synergistic effect was observed. Dual-modified sago starch exhibited lower swelling power, improved gel firmness, and thermal stability with an intact granular structure. Results suggested the potential of gamma irradiation and annealing to induce some novel characteristics in sago starch for extended applications.